iOS 7 development recipes : a problem-solution approach - Hoffman, Joseph; Grönlund, Hans-Eric; Francis, Colin; Grimes, Shawn (Apress Imprint: Apress, 2013)
iOS 7 Development Recipes: A Problem-Solution Approach is your code reference and guide to developing solutions on the iPad, iPhone, and other iOS 7 SDK devices and platforms. This book provides in-depth code samples and discussions for scenarios that developers face every day. You'll find numerous examples of real-world cases that will enable you to build fully functional applications quickly and efficiently. The recipes included in this book are wide in scope and have been geared toward the professional developer. You'll find clear and concise code samples accompanying each recipe, and you will be presented with cutting-edge solutions that bring forth the best that the iOS 7 SDK has to offer. The recipes include: Working with Auto Layout to build flexible user interfaces that adapt to different screen sizes Building applications that incorporate multimedia Building location-aware apps Understanding best practices for application design and development You'll find this book to be an indispensable reference for all your iOS development.